2013
DOI: 10.1038/tp.2012.141
|View full text |Cite
|
Sign up to set email alerts
|

Sustained remission from depressive-like behavior depends on hippocampal neurogenesis

Abstract: Impairment of hippocampal neurogenesis has been associated with the expression of depressive-like symptoms and some studies have suggested neurogenesis as a critical factor in the normalization of behavior by antidepressant (AD) drugs. This study provides robust evidence that ongoing neurogenesis is essential for the maintenance of behavioral homeostasis and that its pharmacological arrest precipitates symptoms commonly found in depressed patients. Further, the incorporation of newly born neurons and astrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
116
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 35 publications
19
116
0
Order By: Relevance
“…In addition, fluoxetine treatment in uCMS rats activated pathways related to cellular respiration and metabolism, a finding in line with the presence of long-lived transcripts (Korostynski et al, 2013;Schwanhausser et al, 2011). Further, consistent with the findings of other studies (Encinas et al, 2006;Mateus-Pinheiro et al, 2013b;Surget et al, 2011), the actions of fluoxetine were more pronounced in neurons than in astrocytes and oligodendrocytes.…”
Section: Ad-specific Transcriptional Changessupporting
confidence: 89%
“…In addition, fluoxetine treatment in uCMS rats activated pathways related to cellular respiration and metabolism, a finding in line with the presence of long-lived transcripts (Korostynski et al, 2013;Schwanhausser et al, 2011). Further, consistent with the findings of other studies (Encinas et al, 2006;Mateus-Pinheiro et al, 2013b;Surget et al, 2011), the actions of fluoxetine were more pronounced in neurons than in astrocytes and oligodendrocytes.…”
Section: Ad-specific Transcriptional Changessupporting
confidence: 89%
“…The resulting persistent HPA axis hyperactivity may set in motion a vicious cycle, in which glucocorticoid abnormalities continue to reduce neurogenesis, ultimately leading to long-term disturbances in stress reactivity and sustained anxiety-like and depressive-like behaviour. This is supported by a rodent study showing that neurogenesis is required for spontaneous recovery from anhedonia, anxiety and cognitive flexibility impairments 4–6 weeks after exposure to chronic stress 137 .…”
Section: Neurogenesis Mood and Anxietymentioning
confidence: 76%
“…Non-pharmacological antidepressant strategies also potently increase neurogenesis and include interventions such as electroconvulsive shock therapy, environmental enrichment, physical exercise and calorific restriction 23,53,123,142,147,148 . Accordingly, neurogenesis is sufficient to confer antidepressant effects in chronically stressed mice 128,149 and to facilitate spontaneous remission from depression-like symptoms 137 . Enhancing neurogenesis through pharmacological or non-pharmacological means may thus be a promising strategy to confer stress resilience or antidepressant effects in patients.…”
Section: Therapeutic Potential Of Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…9, 3840 Chronic stress produces a decrease in hippocampal neurogenesis, 4143 raising the possibility that ablation of neurogenesis may increase the susceptibility to the behavioral effects of stress. Some studies have observed such an increase in stress susceptibility, 44, 45 whereas others have reported that ablation of neurogenesis on its own does not produce an increased sensitivity to the behavioral effects of stress. 6, 46 Our results on the overexpression of BMP4 support the conclusion that stimulation of neurogenesis plays a key role in antidepressant efficacy, but that a reduction in adult hippocampal neurogenesis is not, by itself, sufficient to induce the onset of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%